Planning in the Village Development Process Based on the Village Law in Ganggangpanjang Village, Tanggulangin District, Sidoarjo Regency - Laili, Khusnur (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2019)
This research aims to find out and describe the planning in the process of building a village in GanggangPanjang Village. This research method includes qualitative research, with primary and secondary data collection techniques. Primary data were obtained from observations, interviews and documentation in the GanggangPanjang Village environment with key informants and information. Resource persons in this study were the Secretary of GanggangPanjang Village, Chairman of RW.01 GanggangPanjang Village and the community of GanggangPanjang Village. The results showed that the planning undertaken by the Ganggngpanjang Village Government in developing its village required a number of them: basic information, planning documents.